Ischemic and Hemorrhagic Complications after Intra-Arterial Fibrinolysis in Vertebrobasilar Occlusion - Schulte-Altedorneburg, G. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: To evaluate the incidence and location of hemorrhagic and ischemic lesions after local intra-arterial (IA) fibrinolysis in patients with acute vertebrobasilar occlusion (VBO). METHODS: One hundred forty-three patients with VBO treated with local IA fibrinolysis were retrospectively evaluated. Two different thrombolytic substances, namely urokinase (UK, n = 57 patients) and recombinant tissue plasminogen activator (rtPA, n = 86 patients), were used. Incidence and location of intracranial hemorrhage and ischemic infarction were assessed by means of 403 peri-interventional CT and MR imaging scans. Recanalization success and bleeding rate were correlated with the type and dosage of fibrinolytic agent. Multiple logistic regression was used for statistical analysis. RESULTS: Intracranial hemorrhage was detected in 46 (32%) patients. Bleeding rate was significantly higher for high-dose rtPA than for UK (36% versus 21%, P < .01). Neurologic outcome was worse in patients with postinterventional bleeding (P < .001). Ischemic infarctions were present in 136 (95%) patients. Ischemic lesions of the occipital lobe and thalamus were more frequently seen in the case of successful recanalization than after absent recanalization (P < .005). Occlusion of the postcommunicating segment of the posterior cerebral artery after successful recanalization was seen in 39% of patients. CONCLUSIONS: In acute VBO, bleeding rate after IA rtPA seems to be higher than that using IA UK, especially after high-dose rtPA. Ischemic lesion patterns after successful local IA fibrinolysis are common and correspond to the frequent distal migration of the thrombus. Novel recanalization techniques allowing for endovascular thrombectomy are needed to reduce ischemic and hemorrhagic complications in the treatment of acute VBO.